Single-cell RNA-seq reveals a key role for Vibrio cholerae Mak toxins in Tetrahymena pyriformis killing and bacterial survival - Moon, Jonah M.; Hoque, M. Mozammel; Ronin, Dana; Noorian, Parisa; To, Joyce; Rice, Scott A.; McDougald, Diane; Espinoza-Vergara, Gustavo (Frontiers in Microbiology, 2026)
In the environment, Vibrio cholerae employs multiple strategies to resist predation by heterotrophic protozoa. For example, V. cholerae biofilms release toxic compounds, such as ammonium and pyomelanin, which can kill protists, such as Tetrahymena pyriformis. V. cholerae has also been shown to survive intracellularly and can escape as viable cells inside protozoan-expelled food vacuoles (EFVs). We previously reported that V. cholerae encased in EFVs are hyperinfectious, establishing an important link between anti-protozoal strategies and bacterial virulence. Although the intracellular resistance and escape of V. cholerae in EFVs have been reported, the molecular mechanisms behind this remain poorly understood. Here, we used single-cell transcriptomics of V. cholerae exposed to T. pyriformis and captured a total of 5,344 bacterial cells with heterogeneous gene expression. Cells with the same pattern of gene expression were grouped, resulting in 11 clusters of cells with a unique gene expression profile. Genes encoding outer membrane proteins, F1F0-Na+/H+ ATPase, metabolites, and toxins showed differential expression among the clusters. Furthermore, the motility-associated killing factor (Mak) toxins were differentially expressed. The V. cholerae mutants ΔmakA, ΔmakB, and ΔmakE were not capable of killing T. pyriformis, and ΔmakA and ΔmakE showed reduced survival inside EFVs compared to the wild type. These findings identify Mak toxins as key mediators of V. cholerae resistance to protozoan grazing and survival within EFVs. More broadly, our results provide mechanistic insight into grazing resistance, reveal factors facilitating persistence in EFVs, and underscore the interplay between environmental survival strategies and virulence in pathogenic bacteria.